Exploring factors affecting shareholders’ funds within the conflict of interest posed by the executives of the company - Zhang, Xiang (2010)
This paper investigates the relationship between several factors and the shareholders’ funds within the conflict of interest posed by the executives of the company in 100 companies listed on the London Stock Exchange (LSE). Management decision on corporate performance may affect shareholders’ funds under manager-shareholders conflict arising from asymmetric information. We found a significant relationship between provisions and shareholders’ funds. Furthermore, we also found financial distress, non-audit fees, return on total assets (ROA) and inventory to be significant associated with shareholders’ funds while earning management, executive remunerations and subsidiary are not. The result is robust with respect to different industries.